Paspalum schesslii (Poaceae, Paspaleae), a new species from Mato Grosso (Brazil) with an unusual base chromosome number - Bonasora, Marisa Graciela (2015)
Fil: Bonasora, Marisa Graciela. Universidad de Buenos Aires. Facultad de Agronomía. Cátedra de Botánica Sistemática; Argentina.